Protein and iron intake adequacy among high school girls in Depok, Indonesia - Meirina Khoirunnisa; Yoga Devaera; Umi Fahmida; Fiastuti Witjaksono; Erfi Prafiantini (Indonesian Nutrition Association, 2021)
Introduction: Iron deficiency anemia is the most common type of anemia among adolescent girls. The prevalence of anemia among pregnant women increased from 2013 to 2018, and females age 15-24 years had the highest prevalence of anemia. Therefore, knowing the baseline status of protein and iron intake —particularly animal-sourced protein as the main source of heme iron—is important to design future intervention program. Thus, this study was aimed to assess the protein and iron intake adequacy of High School girls in Depok, Indonesia. Methods: 211 girls from Senior High School in Depok, Indonesia participated in this study. Subjects were selected using a multi-stage random sampling method. A questionnaire was administered to obtain general characteristics. Dietary intake data were obtained using a 3-day non-consecutive 24hr recall 1 weekend 2 weekdays interview. Anthropometric status was measured and calculated. Data were analyzed using IBM SPSS Statistics 20. Spearman’s correlation (significance p<0.05) was used to determine the factors related to protein and iron intake. Results: This population had inadequate intake of energy (97.2%), protein (59.7%), and iron (98.6%). However, intake of fat was higher than recommended in 59.2% of participants. Protein and iron intake were not correlated with age, father’s education, mother’s education, and the number of household member.